Inflammatory Arthritis Prevalence and Health Services Use in the First Nations and Non–First Nations Populations of Alberta, Canada. Issue 4 (9th March 2017) - Barnabe, Cheryl; Jones, C. Allyson; Bernatsky, Sasha; Peschken, Christine A.; Voaklander, Don; Homik, Joanne; Crowshoe, Lynden F.; Esdaile, John M.; El‐Gabalawy, Hani; Hemmelgarn, Brenda
Abstract : Objective: To estimate prevalence of rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic disease (PsD), and crystal‐related arthritis and health care use for inflammatory arthritis in First Nations and non–First Nations patients in Alberta, Canada. Methods: Population‐based cohorts of adults with RA, AS, PsD, and crystal‐related arthritis were defined, with First Nations determination by premium payer status, to estimate prevalence rates. Rates of outpatient primary care, specialist visits, and hospitalizations (all‐cause, inflammatory‐arthritis specific) were estimated. Results: RA affected 3 times as many First Nations residents compared to non–First Nations residents (standardized rate ratio [SRR] 3.2, 95% confidence interval [95% CI] 2.9–3.4). AS and PsD were more prevalent in First Nations (AS 0.6 per 100 residents; SRR 2.7, 95% CI 2.3–3.2 and PsD 0.3 per 100 residents; SRR 1.5, 95% CI 1.3–1.9), whereas crystal‐related arthritis was less prevalent (SRR 0.7, 95% CI 0.6–0.7). First Nations patients were more likely to have primary care visits (SRR 1.7, 95% CI 1.6–1.8) and less likely to have specialist visits (SRR 0.6, 95% CI 0.6–0.7) for RA relative to non–First Nations individuals. In PsD and crystal‐related arthritis, First Nations people had higher rates of cause‐specific hospitalizations. Conclusion: The estimated prevalence of RA, AS, and PsD was higher in the First Nations population, while crystal‐related arthritis was less prevalent compared to the non–First Nations population. First Nations people were more likely to see primary care physicians and were less likely to see specialists for inflammatory arthritis care.